2012
DOI: 10.1213/ane.0b013e31825e7c39
|View full text |Cite
|
Sign up to set email alerts
|

Does Rotational Thromboelastometry (ROTEM) Improve Prediction of Bleeding After Cardiac Surgery?

Abstract: These results suggest that ROTEM data do not substantially improve a model's ability to predict chest tube drainage, beyond frequently used clinical and laboratory parameters. Although several ROTEM parameters were individually associated with CTO, they did not significantly improve goodness of fit when added to statistical models comprising only clinical and routine laboratory parameters. ROTEM does not seem to improve prediction of chest tube drainage after cardiac surgery involving CPB, although its use in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…FIBTEM MCF at the ICU admission demonstrated a higher predictive ability for blood loss than the other tests, but this was not significantly different from plasma fibrinogen level. Lee et al 13 did also investigate ROTEM's predictive value for chest tube drainage after cardiac surgery with CPB in 321 patients. From this study, it was concluded that ROTEM did not substantially improve prediction of chest tube drainage, beyond routine clinical and laboratory variables, although some ROTEM variables were independently associated with chest tube drainage post CPB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FIBTEM MCF at the ICU admission demonstrated a higher predictive ability for blood loss than the other tests, but this was not significantly different from plasma fibrinogen level. Lee et al 13 did also investigate ROTEM's predictive value for chest tube drainage after cardiac surgery with CPB in 321 patients. From this study, it was concluded that ROTEM did not substantially improve prediction of chest tube drainage, beyond routine clinical and laboratory variables, although some ROTEM variables were independently associated with chest tube drainage post CPB.…”
Section: Discussionmentioning
confidence: 99%
“…That ROTEM is only moderately associated with the prediction of blood loss is not surprising, given the numerous factors related to blood loss in cardiac surgical patients, like surgical bleeding, acidosis, CPB time, and body weight. 13,29 However, the advantage of ROTEM compared to plasma fibrinogen levels is that the test has shorter turnaround times, it gives information about the complete haemostatic profile of the patient, and it could therefore be a faster method to guide haemostatic therapy. This study had limited sample size, but was large enough to detect statistically significant AUCs for various ROTEM parameters.…”
Section: Discussionmentioning
confidence: 99%
“…68 Similarly, a prolonged activated partial thromboplastin time (aPTT, a measure of the intrinsic and common coagulation pathways) is independently associated with failure of hemostasis after rFVIIa for refractory hemorrhage. 69 Addressing concomitant deficiencies of other coagulation components before administering rFVIIa is, therefore, prudent. Conversely, the use of high-dose rFVIIa followed by correction of these deficiencies may lead to thromboembolic complications.…”
Section: 61mentioning
confidence: 99%
“…Different studies [135][136][137][138][139][140][141][142] reported these systems to be predictive of risk of increased postoperative bleeding. Other reports have stated the use of different parameters provided by these tests are predictors of both postoperative bleeding and blood product use [143][144][145] .…”
Section: Viscoelastic Methodsmentioning
confidence: 99%